Metabolic network analysis integrated with transcript verification for sequenced genomes - Manichaikul, Ani; Ghamsari, Lila; Hom, Erik F Y; Lin, Chenwei; Murray, Ryan R; Chang, Roger L; Balaji, S; Hao, Tong; Shen, Yun; Chavali, Arvind K; Thiele, Ines; Yang, Xinping; et al. (Nature methods, 2009)
Iterative cycles of metabolic modeling and experimental open reading frame verification in Chlamydomonas reinhardtii lay the groundwork for more accurate gene annotation and provide resources for metabolic engineering. With sequencing of thousands of organisms completed or in progress, there is a growing need to integrate gene prediction with metabolic network analysis. Using Chlamydomonas reinhardtii as a model, we describe a systems-level methodology bridging metabolic network reconstruction with experimental verification of enzyme encoding open reading frames. Our quantitative and predictive metabolic model and its associated cloned open reading frames provide useful resources for metabolic engineering.